Generation Z Within the Workforce and in the Workplace: A Bibliometric Analysis - Benítez-Márquez, María Dolores; Sánchez-Teba, Eva María; Bermúdez-González, Guillermo; Núñez-Rydman, Emma Sofía (Frontiers in Psychology, 2022)
This paper aims to improve the knowledge on Generation Z as employees within workforce and workplace, as well as on the main thematic trends that drive the research on the topic. To this end, and using bibliometric techniques, a sample of 102 publications on this subject from Web of Science between 2009 and 2020 is analysed. Research discusses the most published and cited authors and journals in order to have a broad view of the context of the subject. Later, through a longitudinal view, the study mainly focuses on analysing the evolution of thematic clusters, so as to assess the progress of the themes, as well as the network around the principal motor cluster of each period. The results obtained suggest a hardly developed topic, which started to draw attention in 2018, having still a wide margin for growth. The core of research on the topic has evolved around "Generation-Z" "generations", "workplace", "management" and "attitudes", "leadership", "career" or "learning-teaching-education", although a low keyword stability among periods was noted. There is a need for further development on a variety of aspects regarding this generation and the labour market, as the study shows a clear orientation towards management and generational diversity within the workplace.